MENERAPKAN KONSEP PENGAMBILAN KEPUTUSAN TAKTIS BERBAGAI SITUASI BISNIS : MEMBUAT SENDIRI ATAU MEMBELI “KALENG” PADA PT. DEHO BITUNG - Saptahani, Ayu; Mohezar, Suhana; Abdullahi Suni, Sani; Abdullah, Rudi (AT TARIIZ : Jurnal Ekonomi dan Bisnis Islam, 2024)
This study aims to determine the application of the concept of tactical decision making in various business situations of making your own or buying canned. To assist companies in making the right decision to choose the best alternative action among the available alternatives, it is necessary to calculate costs using various cost methods. One of them is relevant cost. This research is a descriptive study with the approach used is quantitative data, namely in the form of data that is manifested by the numbers of the calculation results. This research was conducted at PT Deho Bitung as the object of research located at Jalan Raya Madidir Bitung. Differential cost analysis is needed in accordance with the problems faced by the company in an effort to increase profits and reduce losses. The results seen from the comparison of differential costs show that the better decision is taken by PT Deho purchased from outside adjuvant cans because the cost is smaller or more efficient than making adjuvant cans themselves.